(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mental health has become an important concern in the higher education system as students often face academic pressure, career uncertainty, social expectations, and personal challenges. Academic institutions play a crucial role in promoting mental health awareness and ensuring the overall wellbeing of students. This study focuses on the role of educational institutions in creating a supportive and healthy environment that encourages mental wellbeing among students. It highlights the importance of institutional initiatives such as counselling services, mental health awareness programs, stress management workshops, peer support groups, and inclusive campus policies. The research also emphasizes the need for integrating mental health education into the academic framework so that students can better understand emotional wellbeing, coping strategies, and the importance of seeking help when required. Additionally, faculty members, administrators, and support staff play a significant role in identifying early signs of stress and guiding students towards appropriate support systems. The study adopts a conceptual and policy-based approach to analyse how academic institutions can effectively promote mental health awareness. It concludes that a holistic institutional strategy, combining policy support, awareness programs, and accessible counselling services, can significantly improve students’ mental wellbeing and contribute to a healthier and more productive academic environment.